Object-Oriented Island Land Cover Change Detection by Iteratively Reweighted Multivariate Statistical Analysis. Issue 2 (4th May 2017) - Gong, Jin-Qi; Liu, Zhengjun; Yan, Qin; Xu, Qiangqiang
ABSTRACT: In studies of changes in island geographic information, a key topic is island land cover change detection using multitemporal remote sensing images; such information can provide good reference for island exploitation, marine resource conservation, marine economic development, and national defense building. This study proposes a fast and easy-to-implement algorithm of object-oriented change detection based on iteratively reweighted multivariate statistical analysis with high-resolution remote sensing images and vector data, improving effects of normal multivariate alternative detection by combining object-oriented technology with probability density function of chi-square distribution. This method builds vectors in feature space with spectral, texture, and spatial structure information of objects segmented based on boundaries and categories of features in vector data. By feature optimization and iterative extension to multivariate statistical analysis for change detection, change regions can be extracted. Experiments on Zhaoshu Island area show that the proposed method is highly effective and accurate in detection of change regions.